The first case record of a female patient with bubonic lymphogranuloma venereum (LGV), serovariant L2b. Issue 5 (22nd February 2012) - Verweij, Stephan P; Ouburg, Sander; de Vries, Harry; Morré, Servaas A; van Ginkel, Cees J W; Bos, Hanna; Sebens, Fré W
Abstract : Since 2003, a lymphogranuloma venereum epidemic has been reported in The Netherlands and other European countries. This epidemic is caused by Chlamydia trachomatis serovariant L2b and has only been seen in men having sex with men. The authors investigated a woman presenting with a bubo in her right groin. The authors showed by real-time PCR that the woman was infected with C trachomatis, serovariant L2b. This is the first reported case study of a female patient with bubonic lymphogranuloma venereum caused by serovariant L2b, which was probably contracted via her bisexual male partner.